Self-Confidence, Vocabulary, and Learning Motivation as Determinants of English Speaking Ability - Pramadanti, Rindika; Achmadi, Rudhi (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2025)
This study aims to examine the influence of self-confidence, vocabulary mastery, and learning motivation on English-speaking ability among students enrolled in English I courses. Using a quantitative research design with structural equation modeling (SEM), the research tested seven hypotheses to identify both direct and indirect relationships among the variables. The results reveal that self-confidence significantly and positively affects learning motivation, indicating that students with higher confidence levels are more motivated to engage in English learning activities. Vocabulary mastery also has a significant positive impact on learning motivation, showing that learners who possess a wide range of vocabulary feel more competent and encouraged to improve their English skills. However, both self-confidence and vocabulary mastery do not have a direct effect on speaking ability. Instead, their influence is mediated through learning motivation. The study further finds that learning motivation has a strong and direct impact on English-speaking ability, acting as the main driving force that enables students to practice and communicate effectively. These findings suggest that psychological (self-confidence), linguistic (vocabulary), and affective (motivation) factors must be developed simultaneously to enhance English-speaking performance. Therefore, fostering motivation and confidence while expanding vocabulary can lead to more effective and sustainable improvements in students’ speaking competence.